Threshold Effects of Sovereign Debt : Evidence From the Caribbean - Drakes, Lisa (IMF Working Papers; Working Paper ;, 2012)
This paper addresses the issue of threshold effects between public debt and economic growth in the Caribbean. The main finding is that there exists a threshold debt to gross domestic product (GDP) ratio of 55-56 percent. Moreover, the debt dynamics begin changing well before this threshold is reached. Specifically, at debt levels lower than 30 percent of GDP, increases in the debt-to-GDP ratio are associated with faster economic growth. However, as debt rises beyond 30 percent, the effects on economic growth diminishes rapidly and at debt levels reaching 55-56 percent of GDP, the growth impacts switch from positive to negative. Thus, beyond this threshold, debt becomes a drag on growth.